Reclaiming the ruins: a multi-criteria decision support framework for the sustainable redevelopment of abandoned public buildings in Nigeria - Mercy Ogunnusi (International Journal of Building Pathology and Adaptation, 2026)
Purpose The proliferation of abandoned public infrastructure represents one of the most consequential yet under-theorised governance challenges confronting developing economies. Nigeria harbours an estimated 4,000 abandoned federal buildings valued at approximately N300 billion, generating compounding social, environmental and fiscal externalities. Despite a substantial descriptive literature on the causes of abandonment, no validated, practitioner-accessible decision-support instrument exists to guide policymakers in selecting an optimal redevelopment pathway for a given asset. This study addresses that gap by developing and validating a multi-criteria decision-making (MCDM) tool for abandoned public infrastructure redevelopment in a Sub-Saharan African context. Design/methodology/approach A sequential explanatory mixed-methods design integrating three complementary phases was adopted. First, a questionnaire survey of 135 built-environment professionals identified the principal drivers of and remedial responses to building abandonment. Second, a TOPSIS MCDM analysis, informed by 167 practitioner ratings, evaluated four redevelopment alternatives, namely Refurbishment, Conversion, Demolition and Outright Sale, across ten sustainability criteria organised under five attributes: Social, Economic, Environmental, Political and Technological (SEEPT). Third, 12 semi-structured interviews with senior practitioners were conducted and analysed thematically using NVivo 20. The resulting decision-support tool, TOPMod, was implemented as an Excel-based interface, pilot-tested with seven academics and externally validated by 15 practitioners. Findings Refurbishment ranked first across all evaluation phases (Pi = 0.844), followed by Conversion (Pi = 0.769), Outright Sale (Pi = 0.454) and Demolition (Pi = 0.333). The SEEPT sustainability framework and thematic analysis consistently corroborated these rankings, affirming the robustness and convergent validity of TOPMod as a practitioner-accessible redevelopment decision instrument. Research limitations/implications The study is geographically bounded to Nigeria's federal building stock, which may limit the direct transferability of findings to other emerging economy contexts with distinct governance structures and property market conditions. Future research should replicate and extend the TOPMod instrument across other Global South jurisdictions and building typologies to enhance its generalisability. Practical implications TOPMod offers policymakers, asset managers and built-environment professionals an empirically grounded, transparent and replicable toolkit for evaluating redevelopment pathways for abandoned public assets. The 5Rs framework (Rethink, Reduce, Reuse, Refurbish, Regulate) provides an actionable policy scaffold directly applicable to infrastructure governance reform across developing economies. Social implications Addressing the estimated N300 billion stock of abandoned federal buildings in Nigeria through evidence-based redevelopment decisions holds significant potential to reverse compounding social, environmental and fiscal externalities, restore community well-being, reclaim productive land and rebuild public trust in government institutions. Originality/value This study presents the first validated MCDM-TOPSIS instrument for abandoned-infrastructure redevelopment decisions in a Sub-Saharan African context. It extends conventional sustainability theory through the novel SEEPT framework, advances the 5Rs policy scaffold tailored specifically to abandoned built assets and delivers an empirically grounded, transferable decision-support toolkit with direct relevance to infrastructure governance across the Global South.